Public finances effictive management as a factor of long-term economic growth - Marta Postuła (Transformation, Integration and Globalization Economic Research (TIGER), 2004)
The paper presents evolution of the Polish fiscal system from the very beginning of Poland's transformation. Effective management of the public funds is crucial for sustaining macroeconomic stability and using public money for financing pro-growth activities. The goal of fiscal reforms, which are currently undertaken, is not only to improve fiscal stance (decrease budget deficit) but also to change structure of public revenues and expenditures.
Keywords: 330; Öffentliche Finanzen; Wirtschaftswachstum; Systemtransformation; Polen